Polish Nurses’ Opinions on the Expansion of Their Competences—Cross-Sectional Study - Kinga Harpula; Anna Bartosiewicz; Jerzy Krukowski (Nursing Reports, 2021)
The development of medical science creates new challenges for nurses to acquire new skills. Thanks to legal changes in Poland, nurses have gained the opportunity to independently provide health services in many areas, including consultations for patients. The aim of the survey is to analyze nurses’ opinions on the expansion of competences in their profession. This is a cross-sectional, descriptive study conducted among 798 nurses using the survey technique. The majority (65.48%) of the respondents believed that they were adequately prepared to take up new competences. Most of the respondents believed that the new competence would improve the efficiency of the healthcare system in Poland (71.06%) and facilitate patients’ access to health services (65.29%). According to the nurses, the scope of nursing advice will mainly concern the promotion of health education, wound treatment and prescribing medications. Age, seniority and education level significantly influenced the nurses’ opinions on the scope of nursing advice. The Mann–Whitney test and the Kruskal–Wallis test were used. A correlation between two quantitative variables was assessed with the Spearman’s rho coefficient. The significance level of p < 0.05 was assumed. The extension of the professional competences of nurses will increase the prestige of the profession and is another step toward introducing the role of Advanced Practice Nurse in Poland.